Computer Aided Diagnosis of Breast Nodule Detection Using Deep Learning Technique - K.M. , Abubakkar Sithik; S. , Kother Mohideen (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, breast cancer is one of the leading causes of cancer-related death in the industrialized countries, and it has the least favorable prognosis among various cancer types. Breast cancer is the fourth most common cause of cancer-related deaths in the Western countries. Tumor specimens contain a variety of healthy cells as well as cancerous cells, and this heterogeneity underlies resistance to various cancer therapies. In this study we aim to facilitate early detection of breast cancer by finding a minimal set of genetic biomarkers that can be used for establishing diagnosis. In this paper, we propose a neural network approach using paired histopathology and immunofluorescence images (for label) and demonstrate classification prediction power. This method can solve the current issue of discrepancy between genomic- or transcriptomic-based and pathology-based tumor purity estimates by improving histological evaluation.